An Overview of Medical Expert Systems - de Vries, P. H.; de Vries Robbé, P. F. (Methods of Information in Medicine, 1985)
Expert systems are an important extension of the research on medical decision making. Their relation to other research in this area is shortly discussed. Fourteen medical expert systems are examined from different perspectives. After a discussion of their goal, domain, and history, the classification of expert systems along the procedural-declarative continuum provides the basis for the analysis of their knowledge representations.As a result of this analysis, types of knowledge are identified that serve as a frame of reference for the comparison of the systems. Subsequently, the central role of these knowledge types in one of the most important tasks of expert systems, explaining, is emphasized. After the knowledge representation, two other components of expert systems are discussed that heavily depend on it: the knowledge acquisition and the man-machine interface. As a conclusion, the status quo of the research on expert systems is outlined and some developments are extrapolated. These developments show a tendency toward the integration of different knowledge types in one system.
Keywords: Computer-aided Diagnosis; Diagnostic Models; Expert Systems; Knowledge Representation; Explanations